Penerapan Deep Learning untuk Meningkatkan Keterampilan Berpikir Kritis Siswa pada Mata Pelajaran IPAS di SD Negeri 54 Seluma - Nike Pratami Mareta; Arbi Tilandri Saputra; Yusril Isa Mahendra; Heny Friantary; Yosi Yulizah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2026)
The implementation of Deep Learning is a learning approach currently being developed in the Indonesian education system to create a conscious, meaningful, and enjoyable learning process. This approach positions students as active learning subjects, constructing knowledge through contextual, reflective, collaborative, and problem-solving-oriented learning experiences. This study aims to describe the implementation of Deep Learning in improving students' critical thinking skills in Natural and Social Sciences (IPAS) at SD Negeri 54 Seluma. The study used a descriptive qualitative approach. The research subjects consisted of the principal, the IPAS teacher, and fourth and fifth grade students at SD Negeri 54 Seluma. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis used the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of Deep Learning can improve students' critical thinking skills through problem-based learning activities, group discussions, environmental exploration, learning reflection, and authentic assessment. Improved critical thinking skills are evident in students' abilities to identify problems, analyze information, present arguments logically, evaluate various alternative solutions, and draw conclusions based on evidence obtained during the learning process. Supporting factors for implementation include teacher competence, principal support, the availability of learning media, and a conducive learning environment. Meanwhile, obstacles identified include limited learning time, variations in students' initial abilities, and limited learning support facilities.